الإستعارة في قصيدة سمط الدرر للحبيب علي بن محمد الحبشي - Fitriyani, Fitriyani; Rini, Rini; Aflisia, Noza (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Simtudduror Habib Ali ibn Muhamad Al-Habsyi and its kind. This type of research is the research of the library used by document researchers, read the books of Simtudduror Habib Ali ibn Muhamad Al-Habsyi and Balaghoh book. Analysis of the data on this research that researchers used is, restrict data by summarizing, the selection of important and systematic things arranged so that clear the results of his research, Data presentation clear and systematic, conclusion and verification, conclusion is the exact description of the object under study. The process of drawing conclusions based on withdrawals from information in data presentation. The result of this research is the meaning of Istia'rah in the picture Simtudduror Habib Ali bin Muhamad Al-Habsyi is very diverse that is about the glory of Muhammad, the attributes of the Prophet Mohammed, the love of a corrupted to his people, the Power of God and the nature of God's compassion on creatures. The type of Istia'rah in the book Simtudduror Habib Ali bin Muhamad Al-Habsyi is the term of Istia'rah Tasrihiyyah 87%, Istia'rah Makniyah of 10%, and Istia'rah Tamtsiliyah 10%.